2020
DOI: 10.1038/s41370-020-0252-0
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of metabolic phenotyping of dried blood spot specimens in rural Chinese women exposed to household air pollution

Abstract: Background Exposure-response studies and policy evaluations of household air pollution (HAP) are limited by current methods of exposure assessment which are expensive and burdensome to participants. Methods We collected 152 dried blood spot (DBS) specimens during the heating and non-heating seasons from 53 women who regularly used biomass-burning stoves for cooking and heating. Participants were enrolled in a longitudinal study in China. Untargeted metabolic phenotyping of DBS were generated using ultra-high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…DBS samples have been evaluated in MS-based metabolic phenotyping and have been used in applications of cancer diagnostics [42], cancer treatments [43], air pollution [44], drug discovery [45], acidemia [46], and pyruvate kinase deficiency [47]. Despite this wide range of applications of DBS samples, there still remain concerns around their volumetric accuracy, This review of microsamples, to our knowledge, is the first of its kind to summarise applications to the metabolic phenotyping literature, wherein we highlight where applications have been successful/advantageous.…”
Section: Traditional Dried Samples: Dry Blood Spots (Dbss)mentioning
confidence: 99%
See 1 more Smart Citation
“…DBS samples have been evaluated in MS-based metabolic phenotyping and have been used in applications of cancer diagnostics [42], cancer treatments [43], air pollution [44], drug discovery [45], acidemia [46], and pyruvate kinase deficiency [47]. Despite this wide range of applications of DBS samples, there still remain concerns around their volumetric accuracy, This review of microsamples, to our knowledge, is the first of its kind to summarise applications to the metabolic phenotyping literature, wherein we highlight where applications have been successful/advantageous.…”
Section: Traditional Dried Samples: Dry Blood Spots (Dbss)mentioning
confidence: 99%
“…To date, studies have successfully performed DBS haematocrit normalisation through potassium content [54], using near-infrared (NIR) spectroscopy [55], haemoglobin measurement using non-contact diffuse reflectance spectroscopy [56], and using wax barriers on DBSs [57]. Despite the development of these normalisation techniques for DBSs, they are yet to be widely adopted in metabolic phenotyping workflows, with many literature examples not implementing a normalisation step in their protocol descriptions [43,44,46,47,55,[58][59][60]. Only two studies have openly reported hct normalisation of their DBS samples as part of their metabolic phenotyping workflow.…”
Section: Approaches To Microsample Collectionsmentioning
confidence: 99%
“…DBS samples have been evaluated in MS-based metabolic phenotyping and have been used in applications of cancer [42,43], air-pollution [44], drug discovery [45], acidemia [46], and pyruvate kinase deficiency [47]. Despite this wide range of applications of DBS samples, there still remains concerns around their volumetric accuracy, particulary in metabolic phenotyping where standardisation of sample volume is required.…”
Section: Traditional Dried Samples: Dry Blood Spots (Dbss)mentioning
confidence: 99%
“…To date, studies have successfully performed DBS haematocrit normalisation through potassium content [54], using near infrared (NIR) spectroscopy [55], haemoglobin measurement using non-contact diffuse reflectance spectroscopy [56], and using wax barriers on DBSs [57]. Despite the development of these normalisation techniques for DBSs, they are yet to be widely adopted in metabolic phenotyping workflows, with many literature examples not implementing a normalisation step in their protocol descriptions [43,44,46,47,55,[58][59][60]. Only two studies have openly reported hct normalisation of their DBS samples as part of their metabolic phenotyping workflow.…”
Section: Traditional Dried Samples: Dry Blood Spots (Dbss)mentioning
confidence: 99%
“…In biological samples, these FAs are present in the forms of free fatty-acids (FFAs) and esterified FAs such as phospholipids, sphingolipids (SPs), glycerides, cholesterol-esters (CEs), FA-esters of hydroxyl-FAs (FAHFAs) and acylcarnitines (ACars) (Fahy et al 2005 ; Han 2016 ; Zhang et al 2023 ). In human blood plasma and serum, for example, FAs are present as FFAs and lipoproteins implicated in numerous pathophysiological processes (Chen et al 2020 , 2023 ; Li et al 2015b , 2023a ; Loo et al 2021 ; Nicholson 2021 ; Wu et al 2021b ; Xia et al 2021 , 2022 ). The biological functions of FAs and their metabolites are diverse including cellular membrane homeostasis (Romero et al 2019 ), energy generation (Lopaschuk et al 2010 ), regulation of transcription-factor activity (Zhang et al 2021 ) and signaling (Dalile et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%